Analisis Perbandingan Komitmen Bidan Koordinator dalam Pencatatan dan Pelaporan PWS KIA di Kabupaten Kapuas - Kristie Hapsari Primaharini; Sutopo Patria Jati; Mateus Sakundarno Adi (Magister Kesehatan Masyarakat, Fakultas Kesehatan Masyarakat, Universitas Diponegoro, 2020)
The midwife's commitment in recording the PWS KIA is a form of responsibility in reporting the PWS KIA and contributing to the achievement of the PWS KIA target. The lack of data and information on PWS KIA can lead to achievement of low and not low targets and cause PWS KIA problems to be resolved. Observation results of the PWS KIA Kapuas report found problems, namely; the report is incomplete, only partially filled in, even the number of formats sent is different for each puskesmas.This research is a qualitative research. Methods of data collection using questionnaires, observation of documents and in-depth interviews. The object of this study was the coordinating midwife and the Head of the Yankesdas Section as the person in charge of PWS KIA in Kapuas Regency.The results of the study are of 2 categories: coordinator midwives with